2022
DOI: 10.3389/fpls.2022.853251
|View full text |Cite
|
Sign up to set email alerts
|

SNAREs Regulate Vesicle Trafficking During Root Growth and Development

Abstract: SNARE (soluble N-ethylmaleimide-sensitive factor attachment protein receptor) proteins assemble to drive the final membrane fusion step of membrane trafficking. Thus, SNAREs are essential for membrane fusion and vesicular trafficking, which are fundamental mechanisms for maintaining cellular homeostasis. In plants, SNAREs have been demonstrated to be located in different subcellular compartments and involved in a variety of fundamental processes, such as cytokinesis, cytoskeleton organization, symbiosis, and b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 156 publications
0
21
0
Order By: Relevance
“…At present, the research on plant SNARE proteins is still in its infancy. Although a large number of SNARE homologous genes have been found in plants through genome sequence alignment, few of them have been biologically verified [ 40 , 41 ]. Transmembrane domain prediction analysis showed that HbOT1 and HbOT2 proteins had four and five transmembrane domains, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…At present, the research on plant SNARE proteins is still in its infancy. Although a large number of SNARE homologous genes have been found in plants through genome sequence alignment, few of them have been biologically verified [ 40 , 41 ]. Transmembrane domain prediction analysis showed that HbOT1 and HbOT2 proteins had four and five transmembrane domains, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…SNAREs are responsible for mediating vesicle-to-target membrane fusion, and the Arabidopsis genome encodes at least 64 SNAREs (Sanderfoot, 2007;Luo et al, 2022). SNARE proteins are classified as Q-SNARE or R-SNARE according to the core SNARE complex residues (glutamine and arginine, respectively) that contribute to structural assembly.…”
Section: Snares Mediate Membrane Fusion During Cell Plate Formationmentioning
confidence: 99%
“…SNARE proteins are classified as Q-SNARE or R-SNARE according to the core SNARE complex residues (glutamine and arginine, respectively) that contribute to structural assembly. Q-SNAREs are further divided into Qa-, Qb-, Qc-, and Qbc-SNAREs (Fasshauer et al, 1998;Bock et al, 2001;Lipka et al, 2007;Luo et al, 2022). SNAREs are involved in a variety of biological processes such as auxin polar transport, vesicle trafficking, autophagy, gravitropism, and biotic and abiotic stress responses (Saito and Ueda, 2009;Larson et al, 2014;Won and Kim, 2020).…”
Section: Snares Mediate Membrane Fusion During Cell Plate Formationmentioning
confidence: 99%
See 1 more Smart Citation
“…Membrane fusion, the last step of vesicular trafficking, is promoted by complex formation of soluble N-ethylmaleimide-sensitive factor attachment receptor proteins (SNAREs) [ 2 ]. SNAREs are located in different subcellular organelles and take part in a series of fundamental processes, for instance, cytokinesis, cytoskeleton organization, symbiosis, growth, and biotic and abiotic stress responses [ 3 , 4 , 5 , 6 ]. For instance, the SYP4 (SYNTAXIN OF PLANTS 4) and SYP6 groups are located in TGN and positively affect tolerance to salinity and osmotic stresses [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%